If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -4i)(x + -2i) = 0 Reorder the terms: (-4i + 2x)(x + -2i) = 0 Reorder the terms: (-4i + 2x)(-2i + x) = 0 Multiply (-4i + 2x) * (-2i + x) (-4i * (-2i + x) + 2x * (-2i + x)) = 0 ((-2i * -4i + x * -4i) + 2x * (-2i + x)) = 0 Reorder the terms: ((-4ix + 8i2) + 2x * (-2i + x)) = 0 ((-4ix + 8i2) + 2x * (-2i + x)) = 0 (-4ix + 8i2 + (-2i * 2x + x * 2x)) = 0 (-4ix + 8i2 + (-4ix + 2x2)) = 0 Reorder the terms: (-4ix + -4ix + 8i2 + 2x2) = 0 Combine like terms: -4ix + -4ix = -8ix (-8ix + 8i2 + 2x2) = 0 Solving -8ix + 8i2 + 2x2 = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), '2'. 2(-4ix + 4i2 + x2) = 0 Factor a trinomial. 2((2i + -1x)(2i + -1x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(2i + -1x)' equal to zero and attempt to solve: Simplifying 2i + -1x = 0 Solving 2i + -1x = 0 Move all terms containing i to the left, all other terms to the right. Add 'x' to each side of the equation. 2i + -1x + x = 0 + x Combine like terms: -1x + x = 0 2i + 0 = 0 + x 2i = 0 + x Remove the zero: 2i = x Divide each side by '2'. i = 0.5x Simplifying i = 0.5xSubproblem 2
Set the factor '(2i + -1x)' equal to zero and attempt to solve: Simplifying 2i + -1x = 0 Solving 2i + -1x = 0 Move all terms containing i to the left, all other terms to the right. Add 'x' to each side of the equation. 2i + -1x + x = 0 + x Combine like terms: -1x + x = 0 2i + 0 = 0 + x 2i = 0 + x Remove the zero: 2i = x Divide each side by '2'. i = 0.5x Simplifying i = 0.5xSolution
i = {0.5x, 0.5x}
| 3q-(-6)=12 | | 2y*27=5y | | 60y-4=173 | | n^2-16n-24=-8 | | 2.3x+34.7=3.8-8.0x | | 7c=2v-20 | | 6x+24+2=-4+-28 | | 5x-8=5y | | (x+5)(x-18)=0 | | -2[4-(3b+2)]=4-2(3b+9) | | 48-31w=-18 | | x+2x+x+3=30 | | 6x+2x+x+3= | | w^2-13w-36=0 | | 4-3x=42 | | 22(2x+y)=29 | | w=.28w+48 | | 2/3x-0,7=1,3x+2 | | -3125=r^5 | | 6x^2+9x-36=0 | | 6x+=20 | | 5sinx+4=3sinx+3 | | f(x)=2x^2+16x+5 | | 3(x-1)+6=-6x(x+7) | | 5(2w-7)=65 | | -4x+3y+15=0 | | 7x-92=252 | | T+10=7t-13 | | -8+2v=-22 | | 2y+2=-4 | | 4(3x+2)=7x+5 | | (-4m+5)(3m-6)=0 |